Short-term effect of percutaneous coronary intervention on ischemic mitral regurgitation - Hazem El-Akabawy; Hamdy Abdul Azeem; EL-Shazly Abdul Khalek (Egyptian Journal of Critical Care Medicine)
Abstract Background The effect of revascularization by PCI for acute coronary syndrome (ACS) on the severity of ischemic mitral regurge (IMR) is still unclear. Objective To evaluate the effect of successful total revascularization by PCI for ACS on the degree of IMR. Methods A total of 240 patients presenting with ACS for the first time were studied by this an open-label, multicenter, prospective clinical trial between July 2015 to February 2017. All patients were subjected for clinical assessment, transthoracic echocardiographic assessment and coronary angiography. The patients divided into two groups: group A; those who had undergone successful total revascularization of a significant coronary artery disease using PCI, and group B; those who had optimal medical treatment with no total revascularization, failed PCI or for CABG. Group A patients subdivided into subgroup I, patients with improvement of the IMR; and subgroup II, patients with no improvement of IMR. Results Only 65% of the patients showed IMR and 149 of them underwent successful complete revascularization by PCI; 68% of them showed IMR improvement and 32% showed no improvement. There was a significant improvement of the IMR degree after total revascularization by PCI. Moreover, this improvement was significant in subgroup I (p < 0.001). Percutaneous coronary intervention, EF and SWMI were significant predictors of IMR improvement following successful complete revascularization. Conclusion Successful total revascularization by early PCI improve IMR degree.